Electrochemical and Electronic Devices

By using lithium difluorophosphate electrolyte and amphiphilic additives in lithium-ion batteries, the thickness changes of the positive electrode mixed layer are controlled, and the problems of interface instability and difficulty in mixing materials are solved, and the battery performance is improved.

JP7660237B2Active Publication Date: 2025-04-10NINGDE AMPEREX TECHNOLOGY LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024017001
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-02-07
Publication Date
2025-04-10
Estimated Expiration
2040-06-05

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have interface instability during circulation and floating charging, resulting in degradation of battery performance and difficult to mix materials during manufacturing, affecting battery performance.

Method used

An electrolyte containing lithium difluorophosphoric acid was used, and an amphiphilic additive was added to the positive electrode mixing layer. By soaking in diacetylated ethanol at 85°C for 120 hours, the thickness change rate of the positive electrode mixing layer was controlled to be less than 10%.

Benefits of technology

It improves the interface stability of lithium-ion batteries, enhances the intermittent cycle and floating charging characteristics of the batteries, and improves the electrochemical performance of the batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660237000001
    Figure 0007660237000001
  • Figure 0007660237000002
    Figure 0007660237000002
  • Figure 0007660237000003
    Figure 0007660237000003
Patent Text Reader

Abstract

To provide electrochemical and electronic devices with improved properties.SOLUTION: An electrochemical device according to the present invention includes a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector, the electrolyte includes a certain amount of lithium difluorophosphate, and the positive electrode mixture layer has a relatively small thickness change rate. The electrochemical device according to the present invention has improved intermittent cycling and float charging characteristics.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of energy storage, in particular electrochemical and electronic devices, especially lithium Regarding U-ion batteries. [Background technology]

[0002] With the development of technology and the increasing demand for mobile devices, electrochemical devices (e.g., lithium The demand for lithium-ion batteries (Li-ion batteries) is increasing significantly, so the characteristics of lithium-ion batteries, especially Higher requirements for intermittent cycling and float charging characteristics of lithium-ion batteries Submit.

[0003] The performance of a lithium-ion battery depends mainly on the properties of the electrodes, electrolyte, and separator. In addition, lithium-ion batteries may experience a decrease in charge / discharge capacity during cycling. One of the causes is poor interface stability. Researchers have developed new battery chemistry systems or introduced other materials into existing battery technologies. However, in the manufacture of lithium-ion batteries, the match of the raw materials is generally Due to problems such as poor mixing and difficulty in compounding, the use of lithium-ion batteries adversely affect the properties.

[0004] In view of this situation, there is a need to provide electrochemical and electronic devices having improved properties. be. Summary of the Invention

[0005] Embodiments of the present invention address, at least to some extent, at least one of the problems existing in the related art. To solve this problem, electrochemical and electronic devices are provided.

[0006] In one aspect, the present invention provides an electrochemical device including a positive electrode, a negative electrode, and an electrolyte. The positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector. The electrolyte contains lithium difluorophosphate, and the difluorophosphate is The content of lithium fluorophosphate is 0.001 wt % to 2 wt %, and the positive electrode mixture layer After immersion in diethyl carbonate at 85°C for 120 hours, the thickness change rate is less than 10%. be.

[0007] According to an embodiment of the present invention, the electrolyte solution includes a carbonate, and the carbonate has a ring structure. The carbonates include cyclic carbonates and linear carbonates.

[0008] According to an embodiment of the present invention, the electrolyte solution includes a carbonate and a carboxylic acid ester, The carbonate is at least one of a cyclic carbonate and a chain carbonate. Includes.

[0009] According to an embodiment of the present invention, the positive electrode mixture layer includes an auxiliary having a hydrophilic group and a lipophilic group.

[0010] According to an embodiment of the present invention, the auxiliary has at least one of the following characteristics: (a) an oxidation potential of 4.5 V or more and a reduction potential of 0.5 V or less; (b) The surface tension is 40 mN / m or less; (c) containing an unsaturated carboxylic acid group; (d) the content of the auxiliary agent is 3000 ppm or less based on the total weight of the positive electrode mixture layer; .

[0011] According to an embodiment of the present invention, the auxiliary agent is 2-dodecyl acrylate, polyethylene glycol Monomethyl ether acrylate, polyethylene glycol dimethacrylate, (2 -Ethylhexyl) acrylate, an acrylate non-ionic fluorocarbon surfactant , dodecyl methacrylate, acrylic acid ester copolymer, maleic acid-acrylic acid copolymer The polymer contains at least one of a copolymer or an ethylene-acrylic acid copolymer.

[0012] According to an embodiment of the present invention, the content X of the lithium difluorophosphate in the electrolyte mg and the reaction area Y m of the positive electrode mixture layer 2 satisfies 10≦X / Y≦100.

[0013] According to an embodiment of the present invention, the electrolyte is a dinitrile compound, a trinitrile compound, a sulfuric acid compound, or a nitrile compound. At least one of fluorocarbonate and unsaturated ethylene carbonate Further includes:

[0014] According to an embodiment of the present invention, the positive electrode mixture layer includes a positive electrode active material, and the positive electrode active material is The lithium-containing transition metal oxides have different di-an sizes.

[0015] According to an embodiment of the present invention, the lithium-containing transition metal oxide is a compound represented by the general formula (1): Compounds, Li a M1 b M2 c M3 d O2(1) Where: M1 is at least one selected from Co, Ni, or Mn; M2 is at least one selected from Mg, Ti, Zr, Ge, Nb, Al, and Sn. and M3 is an element other than Li, M1 and M2; a, b, c and d are 0.5≦a<1.1, 0.8≦b<1.2, 0.002≦c≦0.05, and The relationship 0≦d≦0.05 is satisfied.

[0016] According to an embodiment of the present invention, the lithium-containing transition metal oxide is a material containing Mg, Ti, Zr, G and at least one metal element selected from the group consisting of Nb, Al, and Sn.

[0017] According to a further aspect of the invention, an electronic device comprising an electrochemical device according to the invention is provided. provide.

[0018] Other aspects and advantages of embodiments of the invention are in part described, illustrated, or set forth below. The present invention will now be described through the implementation of an embodiment thereof. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention will be described in detail below with reference to the following examples. The present invention is not limited to the examples. should not be interpreted as

[0020] As used herein, the following terms have the meanings indicated below, unless otherwise specified. do.

[0021] In the description and claims, the phrase "at least one of" A list of items connected by words means any combination of the listed items. For example, if items A and B are listed, "at least one of A and B" can be The phrase "whereas" means only A, only B, or both A and B. If A, B, and C are listed, say "at least one of A, B, and C." The following short phrases are possible: A only, B only, C only, A and B (except C), A and C (except B). , B and C (except A), or all of A, B and C. Term A is a single element. Term B may contain a single element or multiple elements. Item C may contain a single element or multiple elements. The term "one or more" has the same meaning as the term "at least one of."

[0022] The electrodes (positive or negative) of an electrochemical device (e.g., a lithium-ion battery) are generally The active material, the conductive agent, the thickener, the adhesive, and the solvent are mixed, and the mixed slurry is used for current collection. However, there is a problem with the adhesive and the solvent, or the active material and the adhesive. The matching between them is generally not good, making it difficult to mix them. The theoretical capacity of a device varies with the type of active material. As cycling progresses, the electrochemical Devices generally experience a decline in charge / discharge capacity. This is because electrochemical devices Or, the electrode interface changes during discharge. The interface is the interface between the electrode and the electrolyte. , the interface between the current collector and the electrode, and the interface between the electrode active material and the additive. When the quality is reduced, the electrode active material is unable to exert its function.

[0023] The present invention uses a specific positive electrode mixture layer and an electrolyte solution, which reduces the electrochemical To ensure the interface stability of the device, the intermittent cycle characteristics of the electrochemical device and the float charging Improve electrical properties.

[0024] The present invention provides an electrochemical device comprising a positive electrode, a negative electrode and an electrolyte as described below.

[0025] I, positive electrode The positive electrode comprises a positive electrode collector and a positive electrode mixture layer provided on one or two surfaces of the positive electrode collector. The positive electrode mixture layer includes a positive electrode active material layer, and the positive electrode active material layer includes a positive electrode active material. The positive electrode mixture layer may be a single layer or a multi-layer. Each layer may contain the same or a different positive electrode active material.

[0026] Thickness change rate of positive electrode mixture layer One of the main features of the electrochemical device of the present invention is that the positive electrode mixture layer is heated in diethyl carbonate at 85° C. After immersion in water for 120 hours, the thickness change rate of the positive electrode mixture layer is less than 10%. In some embodiments, the positive electrode mixture layer is immersed in diethyl carbonate at 85° C. for 1 hour. After immersion for 20 hours, the thickness change rate of the positive electrode mixture layer is less than 8%. In the example, the positive electrode mixture layer was immersed in diethyl carbonate at 85° C. for 120 hours. In some embodiments, the positive electrode mixture layer has a thickness change rate of less than 6%. The mixture layer was immersed in diethyl carbonate at 85° C. for 120 hours, and then the thickness of the positive electrode mixture layer was In some embodiments, the positive electrode mixture layer is heated to 85° C. and the thickness change rate is less than 5%. After immersion in chill carbonate for 120 hours, the thickness change rate of the positive electrode mixture layer is less than 4%. be.

[0027] The "thickness change rate" of the positive electrode mixture layer is the rate at which the positive electrode mixture layer is immersed in diethyl carbonate at 85°C for 120 This refers to the degree of change in thickness of the positive electrode mixture layer after immersion for a certain period of time compared to before immersion.

[0028] The thickness change rate of the positive electrode mixture layer can be measured by the following method. The positive electrode having the positive electrode mixture layer was punched out into a disk shape with a diameter of 14±0.2 mm to prepare a test piece. The thickness (t0) of the center of the test piece is measured. The test piece is then soaked in diethyl carbonate. Immerse the test piece horizontally and leave it at 85±1℃ for 120±0.3 hours. After removing the test piece and leaving it horizontally at room temperature for 30 minutes, measure the thickness (t1) of the center of the test piece. The thickness change rate of the positive electrode mixture layer is calculated using the following formula. Thickness change rate = (t1-t0) / t0 x 100%.

[0029] The thickness change rate of the positive electrode mixture layer can be increased by adding an auxiliary agent to the positive electrode slurry or by increasing the thickness of the positive electrode active material layer. The amount of the positive electrode active material can be controlled by providing an auxiliary coating layer on the surface. The size of the positive electrode active material particles and the like have almost no effect on the thickness change rate of the positive electrode mixture layer. When the thickness change rate of the positive electrode mixture layer is within the above range, the intermittent cycle characteristics and The battery's float charging characteristics can be significantly improved.

[0030] Auxiliary Agent According to some embodiments of the present invention, the positive electrode mixture layer includes an auxiliary agent.

[0031] In some embodiments, the coagent comprises a hydrophilic group and a lipophilic group.

[0032] In some embodiments, the auxiliary has an oxidation potential of 4.5 V or more and a reduction potential of In some embodiments, the oxidation potential of the auxiliary is 5 V or more. and the reduction potential is 0.3 V or less. The auxiliary agent having the above-mentioned oxidation / reduction potential is , stable electrochemical performance, and excellent intermittent cycle characteristics and float charging of electrochemical devices. This contributes to improving electrical properties.

[0033] In some embodiments, the surface tension of the coagent is 40 mN / m or less. In some embodiments, the surface tension of the auxiliary is less than or equal to 30 mN / m. In some embodiments, the surface tension of the auxiliary is 25 mN / m or less. In some embodiments, the surface tension of the auxiliary is 20 mN / m or less. In some embodiments, the surface tension of the agent is 15 mN / m or less. The surface tension of the auxiliary is 10 mN / m or less. The measurements were taken under NMP solution conditions. The interface between the adhesive layer and the electrochemical device can be improved, and the intermittent cycle characteristics and the float characteristic of the electrochemical device can be improved. Contributes to improved charging characteristics.

[0034] The surface tension of the auxiliary can be measured by the following method. Using a goniometer, measure the NMP solution of the auxiliary agent with a solid content of 1% and measure each sample The surface tension of the auxiliary agent was calculated by taking the average of at least three data points. Obtained.

[0035] In some embodiments, the coagent comprises an unsaturated carboxylic acid group. In the above, the unsaturated carboxylic acid group is an acrylic acid ester, a vinyl ether acrylate, esters of crotonates, propionates, butyrates, or acrylic amines acrylonitrile, vinyl ether-modified carboxylic acid esters Includes at least one.

[0036] In some embodiments, the coagent is 2-dodecyl acrylate, polyethylene glycol. Monomethyl ether acrylate, polyethylene glycol dimethacrylate, ( 2-Ethylhexyl) acrylate, acrylate non-ionic fluorocarbon surfactant Agent, dodecyl methacrylate, maleic acid-acrylic acid copolymer or ethylene-acrylic The polymer contains at least one of the acid copolymers.

[0037] In some embodiments, the content of the auxiliary agent is 3% by weight based on the total weight of the positive electrode mixture layer. In some embodiments, the positive electrode mixture layer has a total weight of 000 ppm or less. In some embodiments, the content of the auxiliary is 2500 ppm or less. The content of the auxiliary agent is 2000 ppm or less based on the total weight of the electrode mixture layer. In the embodiment, the content of the auxiliary agent is 1500p based on the total weight of the positive electrode mixture layer. In some embodiments, the amount of the auxiliary material is less than pm based on the total weight of the positive electrode mixture layer. In some embodiments, the positive electrode mixture layer has a content of the agent of 1000 ppm or less. The content of the auxiliary agent is 500 ppm or less based on the total weight of the composition. The content of the auxiliary agent is 200 ppm or less based on the total weight of the positive electrode mixture layer. When the content of the auxiliary agent is within the above range, the intermittent cycle characteristics and flow characteristics of the electrochemical device are improved. This contributes to improving the battery charging characteristics.

[0038] positive electrode active material The type of the positive electrode active material is not particularly limited, and may be a metal ion (e.g., lithium ion) that is electrochemically charged. In some embodiments, the positive electrode active material may be any material capable of absorbing and releasing ions. is a material that contains lithium and at least one transition metal. , lithium transition metal composite oxides and lithium-containing transition metal phosphate compounds, Not limited to.

[0039] In some embodiments, the positive electrode active material comprises lithium-containing transition metals having different median diameters. In some embodiments, the lithium-containing transition metal oxides have different median diameters. The oxides may have the same or different chemical compositions.

[0040] In some embodiments, the lithium-containing transition metal oxide is represented by the general formula (1): Compounds include Li a M1 b M2 c M3 d O2(1) Where: M1 is at least one selected from Co, Ni, or Mn; M2 is at least one selected from Mg, Ti, Zr, Ge, Nb, Al, and Sn. and M3 is an element other than Li, M1 and M2; a, b, c and d 0.5≦a<1.1, 0.8≦b<1.2, 0.002≦c≦0.05, and The relationship 0≦d≦0.05 is satisfied.

[0041] In some embodiments, M1 includes at least one of Co and Ni. When 1 contains at least one of Co and Ni, the lithium-containing transition metal oxide The content of at least one of Co and Ni in the product is 50 mol % or more, In some embodiments, it is greater than 60 mole percent, and in some embodiments, it is greater than 70 mole percent. % or more, and in some embodiments, 80 mol % or more, or in some embodiments, In embodiments, it is 90 mole % or more.

[0042] In some embodiments, M1 includes Co. In some embodiments, M1 includes When M1 contains Co, the content of Co in the lithium-containing transition metal oxide is The amount is 30 mole % or more, and in some embodiments, 50 mole % or more. In some embodiments, it is 65 mole % or more, and in some embodiments, it is 80 mole % or more. % or more, and in some embodiments, 90 mol % or more, or in some embodiments, In an embodiment, the content is 95 mol % or more. When the lithium-containing transition metal oxide contains Co, the positive This contributes to improving the density of the electrode mixture layer. The Co content in the lithium-containing transition metal oxide is When it is within the above range, the density of the positive electrode mixture layer can be further improved.

[0043] In some embodiments, M2 comprises Mg. In some embodiments, M1 comprises In some embodiments, the Mg content is 0.01 mol % or more. With respect to the content of M1, the content of Mg is 0.05 mol% or more. In some examples, the content of Mg is 0.07 mol % or more relative to the content of M1. In some embodiments, the content of Mg is 0.5 mol % or less relative to the content of M1. In some embodiments, the content of Mg is 0.2 mol% relative to the content of M1. In some embodiments, the content of Mg relative to the content of M1 is 0. In some embodiments, the content of Mg is 1 mol % or less relative to the content of M1. is within the range formed by any two of the above endpoints. When the Mg content is within the above range, the Mg element can function efficiently. , improving the intermittent cycling and float charging characteristics of the electrochemical device.

[0044] In some embodiments, M2 is at least one of Ti, Zr, Ge, Nb, Al, and Sn. It further includes at least one species.

[0045] In some embodiments, M2 is at least one of Ti, Zr, Ge, or Nb. In some embodiments, the content of M1 is preferably Ti, Zr, Ge, or the like. The content of at least one of the elements, Cr, Mn, and Nb, is 0.005 mol % or more. In the embodiment, the content of M1 is at least one of Ti, Zr, Ge, and Nb. The content of each of the above elements is 0.008 mol % or more. The content of at least one of Ti, Zr, Ge or Nb is 0. In some embodiments, the content of Ti, Zr is 0.01 mol % or more. The content of at least one of Ge and Nb is 0.3 mol % or less. In some embodiments, the content of M1 is at least one of Ti, Zr, Ge, and Nb. At least one of the M1 groups is present in an amount of 0.1 mol % or less. The content of at least one of Ti, Zr, Ge and Nb is 0.0 In some embodiments, the content of Ti, Zr, The content of at least one of Ge and Nb is comprised between any two of the above-mentioned end points. The amount of Ti, Zr, Ge or Nb in the lithium-containing transition metal oxide is within the range. When the content of at least one of them is within the above range, the electrochemical device can be subjected to intermittent cycling. This contributes to further improvement of the characteristics and float charging characteristics.

[0046] In some embodiments, M2 further comprises at least one of Al or Sn. In some embodiments, the content of M1 is at least one of Al and Sn. The content of each of the M1 groups is 0.01 mol % or more. The content of at least one of Al and Sn is 0.05 mol% or more. In some embodiments, the content of M1 is at least one of Al and Sn. The content of at least one of M1 is 0.07 mol % or more. The content of at least one of Al and Sn is 0.5 mol% or less. In some embodiments, the content of M1 is at least one of Al and Sn. The content of M1 is 0.2 mol % or less. In some embodiments, the content of M1 is 0.2 mol % or less. On the other hand, the content of at least one of Al and Sn is 0.1 mol % or less. In some embodiments, the content of M1 is at least one of Al and Sn. The content is within the range defined by any two of the above endpoints. When the content of at least one of Al and Sn in the oxide is within the above range, This contributes to further improving the intermittent cycle characteristics and float charge characteristics of the electrochemical device.

[0047] In some embodiments, c satisfies 0.004≦c≦0.02. In the formula, c satisfies 0.006≦c≦0.01. When c is within the above range, lithium The intermittent cycle characteristics and float charge characteristics of the ion battery can be further improved. do.

[0048] The lithium-containing transition metal oxide may contain M2 in various ways, and is not particularly limited. In some embodiments, M2 is present on the lithium-containing transition metal oxide particles. In some embodiments, M2 is uniformly distributed in the lithium-containing transition metal oxide as a solid. In some embodiments, M2 is dispersed in the lithium-containing transition metal oxide. In some embodiments, M2 is a lithium-containing transition metal oxide. A compound layer is formed on the surface of an object.

[0049] In some embodiments, M3 is an alkali metal element other than Li, an alkali metal element other than Mg. Earth metal elements, IIIa group metal elements, IVb group metal elements other than Ti and Zr, and Nb Vb group metal elements, VIb group metal elements, VIIb group metal elements other than Mn, other than Co and Ni Group VIII metal elements, Group Ib metal elements, Zn, Group IIIa metal elements other than Al, Sn and and at least one of P and Bi, a Group IVa metal element other than Pb.

[0050] In some embodiments, M3 is Na, K, Rb, Be, Ca, Sr, Ba, Sc, Y, La, Hf, V, Ta, Cr, Mo, W, Tc, Re, Fe, Ru, Rh, Cu, A It contains at least one of g, Au, Zn, B, Ca, In, Si, P, or Bi.

[0051] In some embodiments, the lithium-containing transition metal oxide does not include M3 (i.e. , d=0).

[0052] In some embodiments, the lithium-containing transition metal oxide is LiNi 0.81 Co 0.16 Al 0.03 O2, LiNi 0.81 Co 0.16 Mg 0.03 O2, LiNi 0.81 Co 0.16 S 0.03 O2, LiNi 0.81 Co 0.16 Ti 0.03 O2, LiCo 0.96 Ti 0.04 O2, LiCo 0.998 Mg 0.0008 Ti 0.0004 Al 0.0008 O2, LiCo 0.994 Mg 0.0024 Ti 0.0012 Al 0.0024 O2, LiCo 0.9988 Mg 0.0008 Ti 0.0004 O2, LiCo 0.9964 Mg 0.0024 Ti 0.0012 O2, or LiCo 0.334 Ni 0.33 Mn 0.33 Mg 0.0024 Ti 0.0012 Al0 .0024 O2.

[0053] The content of each element in the lithium-containing transition metal oxide was measured by inductively coupled plasma (ICP) analysis. Specifically, about 5 g of the lithium-containing transition metal oxide is precisely weighed out, and After placing it in a 00 ml beaker, add 100 ml of aqua regia until the volume of the solution becomes 20-25 ml. Heat and concentrate until the mixture is completely dissolved, then cool and filter the solids using Advantec's quantitative filter paper "No. 5B." The filtrate and washings were separated, and then diluted to a constant volume in a 100 ml measuring flask. ppon Jarrell-Ash Ltd.'s sequential ICP analyzer "IP The elemental content was measured using the IS1000.

[0054] In some embodiments, the lithium-containing transition metal oxide is In some embodiments, the total weight of the positive electrode mixture layer is 99 wt % or less. The content of the lithium-containing transition metal oxide is 97.5 wt % or less. In some embodiments, the lithium-containing transition metal oxide is In some embodiments, the total weight of the positive electrode mixture layer is 97 wt % or less. The content of the lithium-containing transition metal oxide is 98 wt % or less. In some embodiments, the lithium-containing transition metal oxide is In some embodiments, the content of the positive electrode mixture layer is 95 wt % or less. In contrast, the content of the lithium-containing transition metal oxide is 85 wt% or more. In the embodiment, the content of the lithium-containing transition metal oxide is In some embodiments, the amount of the positive electrode mixture layer is 90 wt % or less. In some embodiments, the content of the lithium-containing transition metal oxide is 92 wt % or less. In the embodiment, the content of the lithium-containing transition metal oxide with respect to the total weight of the positive electrode mixture layer is is within the range defined by any two of the above-mentioned end points. When the content of the transition metal oxide is within the above range, the positive electrode mixture layer has high capacity and low resistance. This contributes to the formation of the positive electrode.

[0055] In some embodiments, the lithium-containing transition metal oxide comprises a first particle and a second particle. and the first particles have a first median size and the second particles have a second median size. The first median diameter is smaller than the second median diameter. The diameter D50 can be measured by a known laser diffraction / scattering type particle size distribution measuring device. .

[0056] In some embodiments, the first median diameter is 0.5 μm to 10 μm. In some embodiments, the first median diameter is between 1 μm and 8 μm. In some embodiments, the first median diameter is between 2 μm and 6 μm. In some embodiments, the second median diameter is 11 μm to 30 μm. In some embodiments, the second median diameter is 12 μm to 25 μm. The second median diameter is 13 μm to 20 μm.

[0057] The median diameter of the lithium-containing transition metal oxide can be adjusted by the following method. NaOH is dropped into an acidic aqueous solution of transition metal element M1 to precipitate the hydroxide of M1, and M The hydroxide of 1 is calcined to obtain the oxide of M1. Median diameter of lithium-containing transition metal oxide The median size of the oxide particles was obtained by controlling the precipitation time, precipitate particle size, and calcined M1 oxide particle size. The diameter can be controlled.

[0058] In some embodiments, the discharge capacity of the positive electrode active material is less than the chargeable capacity of the negative electrode active material. This can lead to the unintended deposition of lithium metal on the negative electrode of a lithium-ion battery during charging. can be prevented.

[0059] Positive electrode mixture layer density In some embodiments, the density of the positive electrode mixture layer is 3.5 g / cm 3 That's all. In some embodiments, the density of the positive electrode mixture layer is 3.6 g / cm 3 That's all. In some embodiments, the density of the positive electrode mixture layer is 3.8 g / cm 3 That's all. In one embodiment, the density of the positive electrode mixture layer is 4.6 g / cm 3 Below are some In the embodiment, the density of the positive electrode mixture layer is 4.4 g / cm 3 Below are some In an embodiment, the density of the positive electrode mixture layer is 4.2 g / cm 3 Some examples are as follows. In the embodiment, the density of the positive electrode mixture layer is within the range defined by any two end points described above. When the density of the positive electrode mixture layer is within the above range, the positive electrode mixture layer has good wettability, This contributes to improving the performance of electrochemical devices.

[0060] The density of the positive electrode mixture layer can be measured by the following method. The weight W1 of the positive electrode is measured using an electronic balance with a minimum scale of 1 mg, and the thickness T1 of the positive electrode is measured using a minimum scale of 1 mg. Measure with a μm micrometer, peel off the positive electrode current collector, and measure its weight W2 with an electronic balance. The thickness T2 of the positive electrode current collector was measured with a micrometer, and W1-W2 was determined as the positive electrode mixture layer. The weight of the positive electrode mixture layer is T1-T2, and the thickness of the positive electrode mixture layer is T1-T2. After calculating the volume of the positive electrode mixture layer, the density of the positive electrode mixture layer was calculated from the weight and volume of the positive electrode mixture layer.

[0061] Positive electrode mixture layer thickness In some embodiments, the positive electrode mixture layer has a thickness of 30 μm to 300 μm. In some embodiments, the positive electrode mixture layer has a thickness of 50 μm to 280 μm. In some embodiments, the positive electrode mixture layer has a thickness of 80 μm to 250 μm. In some embodiments, the positive electrode mixture layer has a thickness of 100 μm to 200 μm. In some embodiments, the thickness of the positive electrode mixture layer is 30 μm, 50 μm, 80 μm, 100 μm, μm, 120 μm, 150 μm, 180 μm, 200 μm, or any of the above. It is within the range of two values.

[0062] The thickness of the positive electrode mixture layer can be measured by the following method. The thickness T1 is measured with a micrometer with a minimum scale of 1 μm, and the positive electrode current collector is peeled off. The thickness T2 of the positive electrode mixture layer is measured with a micrometer, and T1-T2 is the thickness of the positive electrode mixture layer.

[0063] Conductive layer In some embodiments, the positive electrode mixture layer may further include a conductive layer including a conductive agent. In some embodiments, the conductive layer does not include a positive electrode active material. Including, but not limited to, lead, carbon black or acetylene black.

[0064] In some embodiments, the content of the conductive agent is 1w In some embodiments, the conductive agent is t% or more based on the total weight of the positive electrode mixture layer. In some embodiments, the total weight of the positive electrode mixture layer is 1.1 wt % or more. In some embodiments, the content of the conductive agent is 1.2 wt % or more. The content of the conductive agent is 3 wt % or less based on the total weight of the positive electrode mixture layer. In the embodiment, the content of the conductive agent is 2 wt % or less based on the total weight of the positive electrode mixture layer. In some embodiments, the content of the conductive agent relative to the total weight of the positive electrode mixture layer is In some embodiments, the amount of the positive electrode mixture layer is 1.5 wt % or less. The content of the conductive agent is within the range defined by any two of the above values. When the content of the conductive agent in the layer is within the above range, it contributes to improving the density and capacity of the positive electrode mixture layer. This improves the cycle characteristics and reduces the load characteristics of the electrochemical device.

[0065] Adhesive In some embodiments, the positive electrode mixture layer includes an adhesive. Examples of suitable materials include, but are not limited to, polyvinylidene fluoride or polytetrafluoroethylene.

[0066] In some embodiments, the content of the adhesive is 1w In some embodiments, the adhesive is t% or more based on the total weight of the positive electrode mixture layer. In some embodiments, the total weight of the positive electrode mixture layer is 1.3 wt % or more. In some embodiments, the adhesive content is 1.5 wt % or more. The content of the adhesive is 4 wt % or less based on the total weight of the positive electrode mixture layer. In the embodiment, the content of the adhesive is 3 wt % or less based on the total weight of the positive electrode mixture layer. In some embodiments, the content of the adhesive relative to the total weight of the positive electrode mixture layer is In some embodiments, the amount of the positive electrode mixture layer is 2 wt % or less. The content of the adhesive is within the range defined by any two of the above values. When the content of the adhesive is within the above range, the adhesion between the positive electrode active material layer and the positive electrode current collector is good. This helps improve the stability of the cathode by avoiding the possibility of the cathode being crushed and falling off. do.

[0067] positive electrode current collector The type of the positive electrode current collector is not particularly limited, and may be any known material that is suitable for a positive electrode current collector. Examples of the positive electrode current collector include aluminum, aluminum alloys, and nickel-plated aluminum. At least one of aluminum, stainless steel, titanium or tantalum, carbon chrome Carbon materials such as, but not limited to, carbonaceous materials, such as carbon paper. In some embodiments, the positive electrode current collector is a metallic material. , aluminum.

[0068] The shape of the positive electrode current collector is not particularly limited. When the positive electrode current collector is made of a metal material, The form of metal is metal foil, metal cylinder, metal coil, metal plate, metal thin film, expanded metal, and paste. The positive electrode current collector may be made of, but is not limited to, carbon material, metal foam, etc. When the positive electrode current collector is a carbon material, the form of the positive electrode current collector includes a carbon plate, a carbon thin film, a carbon cylinder, etc. In some embodiments, the positive electrode current collector is a thin metal film. In the embodiment, the metal thin film is in a mesh shape.

[0069] In some embodiments, the positive electrode current collector has a thickness of 8 μm to 20 μm. In some embodiments, the positive electrode current collector has a thickness of 10 μm to 18 μm. In some embodiments, the thickness of the positive electrode current collector is 12 μm to 15 μm. In an embodiment, the thickness of the positive electrode current collector is within a range formed by any two of the above values. .

[0070] In order to reduce the contact resistance between the positive electrode collector and the positive electrode active material layer, a conductive layer is formed on the surface of the positive electrode collector. Examples of conductive materials include carbon and precious metals such as gold, platinum, and silver. This includes, but is not limited to, the following:

[0071] The method for preparing the positive electrode of the present invention is not limited. For example, the positive electrode can be produced by the following method. Two or more kinds of lithium-containing transition metal oxides having different median diameters can be mixed at a constant weight ratio. The mixture is mixed in a ratio of 0.1 to 1.0, and if necessary, a conductive agent and an adhesive are added. A solvent is added to prepare a slurry for a positive electrode mixture. The obtained positive electrode mixture slurry is applied onto a positive electrode current collector (e.g., aluminum foil), The positive electrode mixture layer is applied to one or two surfaces of the positive electrode current collector. A rolling step is then carried out as necessary to obtain a positive electrode.

[0072] II, electrolyte Another main feature of the electrochemical device of the present invention is that the electrolyte is lithium difluorophosphate. The content of the lithium difluorophosphate relative to the total weight of the electrolyte solution is 0.0 In some embodiments, the total weight of the electrolyte is 0.01 wt % to 2 wt %. The content of the lithium difluorophosphate is 0.01 wt% to 1 wt%. In some embodiments, the lithium difluorophosphate is In some embodiments, the content of tungsten is 0.05 wt% to 0.5 wt%. The content of the lithium difluorophosphate in the electrolyte is 0.1 wt%. In some embodiments, the electrolyte is 0.3 wt % or less based on the total weight of the electrolyte. The lithium difluorophosphate content is 0.001wt%, 0.005wt%, 0.01 wt%, 0.05wt%, 0.1wt%, 0.3wt%, 0.5wt%, 0.8wt%, 1 wt%, 1.2 wt%, 1.5 wt%, 1.8 wt%, 2 wt%, or the above The range is comprised of any two values ​​of the lithium difluorophosphate in the electrolyte. When the content is within the above range, the intermittent cycle characteristics and flow characteristics of the lithium ion battery are improved. This contributes to further improvement of the charge characteristics.

[0073] In some embodiments, the content of the lithium difluorophosphate in the electrolyte solution X mg and the reaction area Y m of the positive electrode mixture layer 2 satisfies 10≦X / Y≦100. In some embodiments, X and Y satisfy 20≦X / Y≦70. In the formula, X and Y satisfy 30≦X / Y≦50. X and Y satisfy the above-mentioned relationship. This will contribute to further improvements in the intermittent cycle characteristics and float charge characteristics of lithium-ion batteries. Give.

[0074] The reaction area of ​​the positive electrode mixture layer can be measured by the following method. The sample was pre-dried for 15 minutes at 350°C under nitrogen flow using a fully automatic surface area measuring device manufactured by Epson. After that, the nitrogen gas relative pressure to atmospheric pressure was precisely adjusted to 0.3. Using gas, the measurement was performed by the nitrogen adsorption BET one-point method using a gas flow method. , the specific surface area of ​​the positive electrode mixture layer (m 2 / g) (i.e., positive electrode active material and additives (adhesive, conductive agent, The specific surface area of ​​the entire positive electrode mixture layer (including adhesive and filler, etc.), and the weight of the positive electrode mixture layer (i.e. A positive electrode mixture containing a positive electrode active material and additives (adhesive, conductive agent, thickener, filler, etc.) The total weight of the entire layer is measured, and the reaction area of ​​the positive electrode mixture layer is calculated by the following formula: . Reaction area = specific surface area of ​​positive electrode mixture layer x weight of positive electrode mixture layer.

[0075] In some embodiments, the electrolyte includes a carbonate. In some embodiments, the electrolyte includes carbonates and carboxylic acid esters. The carbonate is at least one of a cyclic carbonate and a chain carbonate. Carbonates or combinations of carbonates with carboxylic acid esters are also included. This contributes to the formation of a passivation film on the surface of the electrochemical device. The cycle characteristics and float charge characteristics can be improved.

[0076] In some embodiments, the content of the carbonate relative to the total weight of the electrolyte is In some embodiments, the content of the electrolyte is 10 wt % to 90 wt % based on the total weight of the electrolyte. The content of the carbonate is 15 wt% to 85 wt%. In the electrolyte, the content of the carbonate is 20 wt % to 7 wt % based on the total weight of the electrolyte. In some embodiments, the carbohydrate is 5 wt % based on the total weight of the electrolyte. In some embodiments, the content of the electrolyte is 25 wt% to 65 wt%. The content of the carbonate in the total weight of the solution is 10 wt%, 15 wt%, 20 wt%, t%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 6 0wt%, 70wt%, 80wt%, 90wt%, or any two of the above values When the content of carbonate in the electrolyte is within the above range, , which contributes to further improvement of the intermittent cycle characteristics and float charge characteristics of the electrochemical device.

[0077] In some embodiments, the cyclic carbonate is ethylene carbonate (E C), propylene carbonate (PC) and butylene carbonate, or In some embodiments, the cyclic carbonate includes, but is not limited to, has 3 to 6 carbon atoms.

[0078] In some embodiments, examples of the linear carbonate include dimethyl carbonate, ethylene carbonate, ethylene glycol carbonate, ethylene glycol ether ... Diethyl methyl carbonate, diethyl carbonate (DEC), methyl-n-propyl carbonate Chain carbonates such as ethyl-n-propyl carbonate, di-n-propyl carbonate, etc. The present invention includes, but is not limited to, one or more of the following: Examples of substituted linear carbonates are bis(fluoromethyl)carbonate, bis(di fluoromethyl)carbonate, bis(trifluoromethyl)carbonate, bis(2- fluoroethyl) carbonate, bis(2,2-difluoroethyl) carbonate, bis (2,2,2-trifluoroethyl)carbonate, 2-fluoroethylmethylcarbonate methyl carbonate, 2,2-difluoroethyl methyl carbonate and 2,2,2-trifluoroethyl Examples of suitable amines include, but are not limited to, one or more of dimethyl carbonate, dimethyl ester ...

[0079] In some embodiments, the carboxylic acid ester is a linear carboxylic acid ester or The compound contains at least one of cyclic carboxylic acid esters.

[0080] In some embodiments, the cyclic carboxylic acid ester is exemplified by γ-butyrolactone. and gamma-valerolactone, and the like. In some embodiments, some of the hydrogen atoms of the cyclic carboxylic acid ester are replaced by fluorine. may be substituted.

[0081] In some embodiments, examples of the linear carboxylic acid ester include methyl acetate, ethyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, sec-butyl acetate, isobutyl acetate butyl acetate, t-butyl acetate, methyl propionate, ethyl propionate, propionate propionate, isopropyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl isobutyrate ethyl isobutyrate, methyl valerate, ethyl valerate, methyl pivalate and ethyl pivalate Examples of suitable fluorochemicals include, but are not limited to, one or more of the following: In the above, some of the hydrogen atoms of the chain carboxylate may be substituted with fluorine. In some embodiments, examples of fluorine-substituted linear carboxylic acid esters include are methyl trifluoroacetate, ethyl trifluoroacetate, propyl trifluoroacetate, Includes butyl trifluoroacetate and 2,2,2-trifluoroethyl trifluoroacetate. But not limited to these.

[0082] In some embodiments, the electrolyte is a dinitrile compound, a trinitrile compound, a sulphonate compound, At least one of tetrafluoroethylene, fluorocarbonate, or unsaturated ethylene carbonate It further comprises seeds.

[0083] In some embodiments, examples of the dinitrile compounds include succinonitrile, glutathione, adiponitrile, adiponitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, Tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile Glutaronitrile, 2,2,4,4-Tetramethylglutaronitrile, 1,4-dicyanopentanitrile 1,4-dicyanopentane, 1,2-dicyanobenzene, 1,3-dicyanobenzene , 1,4-dicyanobenzene, ethylene glycol bis(propionitrile) ether, 3,5-Dioxa-pimelonitrile, 1,4-bis(cyanoethoxy)butane, diethyl Glycol bis(2-cyanoethyl) ether, triethylene glycol bis(2-cyanoethyl) ether tetraethylene glycol bis(2-cyanoethyl) ether, tetraethylene glycol bis(2-cyanoethyl) ether, 1,3-Bis(2-cyanoethoxy)propane, 1,4-Bis(2-cyanoethoxy)butane 1,5-bis(2-cyanoethoxy)pentane, ethylene glycol bis(4-cyano anhydrous butyl ether, 1,4-dicyano-2-butene, 1,4-dicyano-2-methyl -2-butene, 1,4-dicyano-2-ethyl-2-butene, 1,4-dicyano-2,3 -Dimethyl-2-butene, 1,4-dicyano-2,3-diethyl-2-butene, 1,6- One of dicyano-3-hexene or 1,6-dicyano-2-methyl-3-hexene Including, but not limited to, species or multi-species.

[0084] In some embodiments, the trinitrile compound is exemplified by 1,3,5-pentanediol. Tricarbonitrile, 1,2,3-propanetricarbonitrile, 1,3,6-hexanetricarbonitrile Hexanetricarbonitrile, 1,2,6-hexanetricarbonitrile, 1,2,3-tris(2 -cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)butane, 1, 1,1-Tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxy (dimethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-Tris(cyanoethoxy)heptane, 1,2,6-Tris(cyanoethoxy)heptane ) Hexane and 1,2,5-tris(cyanoethoxy)pentane Including, but not limited to:

[0085] In some embodiments, examples of the sultones include 1,3-propane sultone, 1-furan sultone, Fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro Fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl 1-propene-1,3-propane sultone, 3-methyl-1,3-propane sultone, -1,3-sultone, 2-propene-1,3-sultone, 1-fluoro-1-propene- 1,3-sultone, 2-fluoro-1-propene-1,3-sultone, 3-fluoro-1 -propene-1,3-sultone, 1-fluoro-2-propene-1,3-sultone, 2- Fluoro-2-propene-1,3-sultone, 3-fluoro-2-propene-1,3-sultone sultone, 1-methyl-1-propene-1,3-sultone, 2-methyl-1-propene-1 ,3-sultone, 3-methyl-1-propene-1,3-sultone, 1-methyl-2-propene 2-Methyl-2-propene-1,3-sultone, 3-Methyl- 2-Propene-1,3-sultone, 1,4-butane sultone, 1,5-pentane sultone methylenemethane disulfonate and ethylenemethane disulfonate or various kinds, but are not limited to these.

[0086] In some embodiments, the fluorocarbonate has the formula C=O(OR1)(OR2). wherein R1 and R2 are each independently an alkyl group having 1 to 6 carbon atoms. wherein at least one of R1 and R2 is selected from the group consisting of an alkyl group, a halogenated alkyl group, and a halogenated alkyl group. The other is selected from fluoroalkyl groups having 1 to 6 carbon atoms, and R1 and R2 optionally form a 5- to 7-membered ring together with the atoms to which they are attached.

[0087] In some embodiments, the fluorocarbonate is exemplified by fluoroethylene carbonate. Carbonate, cis-4,4-difluoroethylene carbonate, trans-4,4-difluoro 4,5-Difluoroethylene carbonate, 4-fluoro- 4-Methylethylene carbonate, 4-fluoro-5-methylethylene carbonate, charcoal Trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate and ethyl trifluorocarbonate These include, but are not limited to, one or more of the following:

[0088] In some embodiments, the unsaturated ethylene carbonate is exemplified by vinylene carbonate. methylvinylene carbonate, ethylvinylene carbonate, 1,2-dimethyl Vinylene carbonate, 1,2-diethylvinylene carbonate, fluorovinylene carbonate Carbonate, Trifluoromethylvinylene carbonate, Vinyl ethylene carbonate, 1 -Methyl-2-vinylethylene carbonate, 1-ethyl-2-vinylethylene carbonate 1-n-propyl-2-vinyl ethylene carbonate, 1-methyl-2-vinyl ethylene carbonate ethylene carbonate, 1,1-divinylethylene carbonate, 1,2-divinylethylene ethylene carbonate, 1,1-dimethyl-2-methylene ethylene carbonate and 1,1-di ethyl-2-methylene ethylene carbonate, etc. In some embodiments, the unsaturated ethylene carbonate is Vinylene carbonate is included because it is easy to handle and can achieve even more excellent effects.

[0089] In some embodiments, the electrolyte further comprises a cyclic ether. In the examples, examples of the cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, Furan, 1,3-dioxolane, 2-methyl-1,3-dioxolane, 4-methyl-1, 3-dioxolane, 1,3-dioxane, 1,4-dioxane and dimethoxypropane including, but not limited to, one or more of the following:

[0090] In some embodiments, the electrolyte further comprises a chain ether. In the examples, examples of the chain ethers include dimethoxymethane, 1,1-dimethoxyethane, , 1,2-dimethoxyethane, diethoxymethane, 1,1-diethoxyethane, 1,2- Diethoxyethane, ethoxymethoxymethane, 1,1-ethoxymethoxyethane and 1, 2-Ethoxymethoxyethane and the like. stomach.

[0091] In some embodiments, the electrolyte further comprises a phosphorus-containing organic solvent. In the embodiment, the phosphorus-containing organic solvent is exemplified by trimethyl phosphate, triethyl phosphate, etc. , dimethyl ethyl phosphate, methyl diethyl phosphate, ethylene methyl phosphate, ethylene phosphate Ethyl phosphate, triphenyl phosphate, trimethyl phosphite, triethyl phosphite, thi triphenyl, tris(2,2,2-trifluoroethyl) phosphate and tris(2, 2,3,3,3-pentafluoropropyl), etc. However, the present invention is not limited to the above.

[0092] In some embodiments, the electrolyte further comprises a sulfur-containing organic solvent. In the embodiments, examples of the sulfur-containing organic solvent include sulfolane, 2-methylsulfolane, 3-Methylsulfolane, dimethylsulfone, diethylsulfone, ethylmethylsulfone, Methyl propyl sulfone, dimethyl sulfoxide, methyl methanesulfonate, methanesulfonate Ethyl ethanesulfonate, methyl ethanesulfonate, ethyl ethanesulfonate, dimethyl sulfate, sulfuric acid Diethyl and dibutyl sulfate, or one or more of the following: In some embodiments, some of the hydrogen atoms of the sulfur-containing organic solvent are replaced by fluorine. This may also be the case.

[0093] In some embodiments, the electrolyte further comprises a fluorine-containing solvent. In an embodiment, the aromatic fluorine-containing solvent is fluorobenzene, difluorobenzene, Trifluorobenzene, tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene These include one or more of the following: Not limited to.

[0094] In some embodiments, the electrolyte comprises a compound containing a sulfur-oxygen double bond. In some embodiments, the compound containing a sulfur-oxygen double bond is Examples of compounds include cyclic sulfates, linear sulfates, linear sulfonates, and cyclic sulfuric acid esters. One or more of the following: sulfuric acid esters, linear sulfite esters, and cyclic sulfite esters Including, but not limited to, species.

[0095] In some embodiments, the cyclic sulfate is exemplified by 1,2-ethylene glycol. 1,2-Propylene glycol sulfate, 1,3-Propylene glycol Cholesterol sulfate, 1,2-butylene glycol sulfate, 1,3-butylene glycol Cholesterol sulfate, 1,4-butylene glycol sulfate, 1,2-pentylene glycol Lithium sulfate, 1,3-pentylene glycol sulfate, 1,4-pentylene 1,5-pentylene glycol sulfate, etc. Including, but not limited to, one or more types.

[0096] In some embodiments, examples of the linear sulfate ester include dimethyl sulfate, ethyl sulfate, These include, but are not limited to, one or more of methyl and diethyl sulfate.

[0097] In some embodiments, the linear sulfonic acid ester is exemplified by fluorosulfonic acid. Fluorosulfonate esters such as methyl and ethyl fluorosulfonate, methanesulfonate Methyl methanesulfonate, ethyl methanesulfonate, butyl dimethanesulfonate, 2-(methanesulfonate Methyl 2-(methanesulfonyloxy)propionate and Ethyl 2-(methanesulfonyloxy)propionate These include, but are not limited to, one or more of the following:

[0098] In some embodiments, examples of the linear sulfite ester include dimethyl sulfite, sulfite ethyl methyl sulphite and diethyl sulphite. I can't.

[0099] In some embodiments, the cyclic sulfite is exemplified by 1,2-ethylene glycol. 1,2-Propylene glycol sulfite, 1,3-Propylene glycol sulfite 1,2-Butylene glycol sulfite, 1,3-Butylene glycol sulfite Butylene glycol sulfite, 1,4-butylene glycol sulfite, 1,2 -Pentylene glycol sulfite, 1,3-pentylene glycol sulfite , 1,4-pentylene glycol sulfite and 1,5-pentylene glycol sulfite These include, but are not limited to, one or more of the following: acid esters, and the like.

[0100] In some embodiments, the electrolyte further comprises one or more acid anhydrides. In some embodiments, examples of the acid anhydride include cyclic phosphoric acid anhydride, carboxylic acid anhydride, , disulfonic anhydrides and carboxylic acid sulfonic anhydrides, , but not limited to these.

[0101] In some embodiments, the cyclic phosphoric anhydride is exemplified by trimethylphosphonic anhydride. triethylphosphonic anhydride and tripropylphosphonic anhydride, or Various types include, but are not limited to:

[0102] In some embodiments, examples of the carboxylic acid anhydride include succinic anhydride, glutaric anhydride, The present invention is not limited to one or more of maleic acid and maleic anhydride.

[0103] In some embodiments, the disulfonic anhydride is exemplified by ethane disulfonic anhydride. and propanedisulfonic anhydride. do not have.

[0104] In some embodiments, the carboxylic acid sulfonic acid anhydride is exemplified by sulfobenzoic acid. Anhydride, sulfopropionic anhydride, and sulfobutanoic anhydride. Including, but not limited to:

[0105] The electrolyte is not particularly limited, and any substance known as an electrolyte may be used. In the case of lithium secondary batteries, lithium salts are usually used. Examples of electrolytes are LiPF6, Li BF4, LiClO4, LiAlF4, LiSbF6, LiTaF6, LiWF7, etc. Inorganic lithium salts, lithium tungstates such as LiWOF5, HCO2Li, CH3 CO2Li, CH2FCO2Li, CHF2CO2Li, CF3CO2Li, CF3CH 2CO2Li, CF3CF2CO2Li, CF3CF2CF2CO2Li, CF3CF2 Lithium carboxylates such as CF2CF2CO2Li, FSO3Li, CH3SO3L i, CH2FSO3Li, CHF2SO3Li, CF3SO3Li, CF3CF2SO3 Li, CF3CF2CF2SO3Li, CF3CF2CF2CF2SO3Li, etc. Lithium phosphate salts, LiN(FCO)2, LiN(FCO)(FSO2), LiN(FSO2) 2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO 2)2, Lithium cyclic 1,2-perfluoroethane disulfonylimide, Lithium cyclic 1 ,3-Perfluoropropanedisulfonylimide, LiN(CF3SO2)(C4F9SO 2), Lithium imide salts such as LiC(FSO2)3, LiC(CF3SO2)3, LiC( Lithium methylate salts such as C2F5SO2)3, lithium bis(malonato)borate , lithium (malonato)borate salts such as lithium difluoro(malonato)borate; Lithium tris(malonato)phosphate, lithium difluorobis(malonato)phosphate Lithium(malonato)phosphate, lithium tetrafluoro(malonato)phosphate, etc. Phosphate salts, and LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4( CF3SO2)2, LiPF4(C2F5SO2)2, LiBF3CF3, LiBF3C2 F5, LiBF3C3F7, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF Fluorine-containing organic lithium salts such as 2(CF3SO2)2 and LiBF2(C2F5SO2)2 , lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, etc. Which lithium oxalato borates, lithium tetrafluoro(oxalato)phosphates Lithium difluorobis(oxalato)phosphate, Lithium tris(oxalato)phosphate ) phosphate salts, including lithium (oxalato)phosphate salts. Not limited.

[0106] In some embodiments, the electrolyte is LiPF6, LiSbF6, LiTaF6, FS O3Li, CF3SO3Li, LiN(FSO2)2, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, Lithium cyclic 1,2-perfluorinated Lithium Cyclic 1,3-Perfluoropropane Disulfonyl Imide Imide, LiC(FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, L iBF3CF3, LiBF3C2F5, LiPF3(CF3)3, LiPF3(C2F5)3 , lithium difluoro(oxalato)borate, lithium bis(oxalato)borate or or lithium difluorobis(oxalato)phosphate. Improved output characteristics, high-power charge / discharge characteristics, high-temperature storage characteristics, and cycle characteristics of gas and chemical equipment This contributes to making

[0107] The content of the electrolyte is not particularly limited as long as the effect of the present invention is not impaired. In an embodiment, the total molar concentration of lithium in the electrolyte is 0.3 mol / L or more; More than 0.4 mol / L, or more than 0.5 mol / L. , the total molar concentration of lithium in the electrolyte is less than 3 mol / L, less than 2.5 mol / L, In some embodiments, the lithium content in the electrolyte is less than 2.0 mol / L. The total molar concentration of the electrolyte is within the range of any two of the above values. Within the above range, the amount of lithium as a charged particle is not too small, and the viscosity Since the amount of the conductive material can be kept within an appropriate range, it is easy to ensure good electrical conductivity.

[0108] When two or more electrolytes are used in combination, the electrolytes are monofluorophosphate, borate, oxalate, etc. The salt includes at least one salt selected from the group consisting of acid salts and fluorosulfonates. In some embodiments, the electrolyte is selected from the group consisting of monofluorophosphate, oxalate, and fluorosulfate. In some embodiments, the electrolyte comprises a salt selected from the group consisting of lithium phosphates. In some embodiments, the electrolyte may contain monofluorophosphate salts based on the total weight of the electrolyte. containing a salt selected from the group consisting of acid salts, borates, oxalates and fluorosulfonates The amount may be greater than 0.01 wt%, or greater than 0.1 wt%. , monofluorophosphate, borate, oxalate and fluoro based on the total weight of the electrolyte The content of the salt selected from the group consisting of sulfonates is less than 20 wt% or less than 10 wt%. In some embodiments, monofluorophosphate, borate, oxalate and The content of the salt selected from the group consisting of fluorosulfonates and fluorosulfonates is any two of the above values. is within the range consisting of

[0109] In some embodiments, the electrolyte is a monofluorophosphate, a borate, an oxalate, or and fluorosulfonates, and one or more other substances Other salts include the lithium salts exemplified above, and some In the examples, LiPF6, LiN(FSO2)(CF3SO2), LiN(CF3SO 2)2, LiN(C2F5SO2)2, Lithium cyclic 1,2-perfluoroethane disulfide Nirimide, Lithium Cyclic 1,3-Perfluoropropanedisulfonylimide, LiC( FSO2)3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiBF3CF3 , LiBF3C2F5, LiPF3(CF3)3, and LiPF3(C2F5)3. In some embodiments, the other salt is LiPF6.

[0110] In some embodiments, the content of other salts based on the total weight of the electrolyte is 0.0 In some embodiments, the total amount of the electrolyte is greater than 1 wt %, or greater than 0.1 wt %. The content of other salts by weight is less than 20wt%, less than 15wt%, or less than 10wt%. In some embodiments, the content of other salts is less than any of the above. The electrolyte is preferably a salt having a content of 0.1 to 0.25% by weight. It contributes to balancing electrical conductivity and viscosity.

[0111] The electrolyte may contain, in addition to the above-mentioned solvent, additive, and electrolyte salt, a negative electrode film forming agent as required. The additive may include other additives such as a positive electrode protector, an overcharge inhibitor, etc. Common additives used in secondary batteries can be used. Examples include vinylene carbonate. Carbonate, succinic anhydride, biphenyl, cyclohexylbenzene, 2,4-difluoroacetate These include, but are not limited to, nisole, propane sultone, propene sultone, and the like. These additives may be used alone or in any combination. The content of these additives in the liquid is not particularly limited, and may be appropriately determined depending on the type of the additive. In some embodiments, the content of the additive with respect to the total weight of the electrolyte may be set. is less than 5 wt%, is in the range of 0.01 wt% to 5 wt%, or is less than 0.2 wt% % to 5wt%.

[0112] III, negative electrode The negative electrode comprises a negative electrode current collector and a negative electrode mixture layer provided on one or two surfaces of the negative electrode current collector. The negative electrode mixture layer includes a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material. The active material layer may be a single layer or a multi-layer. The layers may contain the same or different negative electrode active materials. Any material capable of reversibly inserting and desorbing metal ions. In order to prevent the unintentional deposition of lithium metal on the negative electrode during charging, The available capacity is greater than the discharge capacity of the positive electrode active material.

[0113] As the current collector for holding the negative electrode active material, any known current collector may be used. Examples of metals include aluminum, copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper. do.

[0114] When the negative electrode current collector is made of a metal material, the negative electrode current collector may be in the form of a metal foil, a metal cylinder, a metal coil, or the like. , metal plate, metal thin film, expanded metal, punched metal, foamed metal, etc. In some embodiments, the negative electrode current collector is a thin metal film. In some embodiments, the negative electrode current collector is a copper foil. The electrode current collector is a rolled copper foil produced by a rolling method or an electrolytic copper foil produced by an electrolytic method.

[0115] In some embodiments, the thickness of the negative electrode current collector is greater than 1 μm, or greater than 5 μm. In some embodiments, the thickness of the negative electrode current collector is less than 100 μm or less than 50 μm. In some embodiments, the thickness of the negative electrode current collector can be any two of the values ​​above. It is within the scope of what can be achieved.

[0116] The negative electrode active material is not particularly limited, and can be any material capable of reversibly absorbing and releasing lithium ions. Examples of the negative electrode active material include carbon materials such as natural graphite and artificial graphite, silicon (Si), and silicon dioxide (SiO2). Metals such as Sn (tin) and oxides of metal elements such as Si and Sn are included. There is no limitation. The negative electrode active materials may be used alone or in combination.

[0117] The negative electrode mixture layer further includes a negative electrode adhesive. The negative electrode adhesive acts to adhere particles of the negative electrode active material to each other and The type of the negative electrode adhesive is not particularly limited. The material is not limited as long as it is stable to the electrolyte or the solvent used during the manufacture of the electrodes. In some embodiments, the negative electrode adhesive comprises a resin adhesive. An example of the resin adhesive is fluororesin. Base resin, polyacrylonitrile (PAN), polyimide resin, acrylic resin, polyolefm Fin resin, etc., but are not limited to these. Aqueous solvent is used to prepare a slurry for the negative electrode mixture. When preparing the negative electrode adhesive, carboxymethyl cellulose (CMC) or its salt, Styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinylidene These include, but are not limited to, alcohol and the like.

[0118] The negative electrode can be prepared by the following method. The negative electrode mixture slurry containing the agent is applied to both sides of the negative electrode current collector by rolling after drying. By forming an electrode mixture layer, a negative electrode is obtained.

[0119] IV, separator A separator is usually provided between the positive electrode and the negative electrode to prevent short circuits. In this case, the electrolyte of the present invention is usually impregnated into the separator before use.

[0120] The material and shape of the separator are not particularly limited as long as they do not significantly impair the effects of the present invention. The separator is made of a material that is stable against the electrolyte of the present invention, such as a resin, glass fiber, or inorganic material. In some embodiments, the separator may be a multi-layered material having excellent liquid retention. Porous sheets or nonwoven fabrics, etc. Resin or glass fiber separator materials Examples are polyolefins, aromatic polyamides, polytetrafluoroethylene, polyethers. Examples of suitable filters include, but are not limited to, fluorosulfone, glass filters, etc. In some embodiments, the separator is made of a glass filter. The polyolefin is polyethylene or polypropylene. In the above, the polyolefin is polypropylene. They may be used alone or in any combination.

[0121] The separator may be a material formed by laminating the above-mentioned materials. An example of the material is a polyester. Three-layer separators made by laminating propylene, polyethylene, and polypropylene in that order. Including, but not limited to:

[0122] Examples of inorganic materials are oxides such as aluminum oxide and silicon dioxide, aluminum nitride, Nitrides such as silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The inorganic form includes, but is not limited to, particulate or fibrous. Not limited to.

[0123] The separator is in the form of a film, examples of which include nonwoven fabric, woven fabric, microporous In the form of a film, the separator may be in the form of, but not limited to, a film. The pore size is 0.01 μm to 1 μm, and the thickness is 5 μm to 50 μm. In addition to the film-like separator, the following separators can also be used: The composite porous layer containing the inorganic particles is attached to the positive electrode and / or the positive electrode using a resin adhesive. Alternatively, a separator formed on the surface of the negative electrode can be used. For example, Aluminum oxide with 90% particle size less than 1μm is applied to both sides of the positive electrode using fluorine resin. Alternatively, a separator formed by forming a porous layer on a substrate may be used.

[0124] The separator may have any thickness. In some embodiments, the separator may have a thickness of In some embodiments, the thickness is greater than 1 μm, greater than 5 μm, or greater than 8 μm. The thickness of the separator is less than 50 μm, less than 40 μm, or less than 30 μm. In some embodiments, the thickness of the separator is comprised of any two of the values ​​listed above. When the thickness of the separator is within the above range, the insulating property and mechanical strength are improved. It is possible to ensure the rate characteristics and energy density of the electrochemical device while ensuring the reliability.

[0125] When a porous material such as a porous sheet or nonwoven fabric is used as the separator, the separator The porosity of the separator is optional. In some embodiments, the porosity of the separator is 20 %, greater than 35%, or greater than 45%. The porosity of the plate is less than 90%, less than 85%, or less than 75%. The porosity of the separator is within a range consisting of any two of the above values. When the porosity of the separator is within the above range, the insulating property and mechanical strength are ensured. The resistance of the membrane can be suppressed, and the electrochemical device can have good rate characteristics. This can be done.

[0126] The average pore size of the separator is also arbitrary. In some embodiments, the average pore size is less than 0.5 μm or less than 0.2 μm. In some embodiments, the separator has an average pore size of more than 0.05 μm. The average pore size of the separator is within the range defined by any two of the above values. If the average pore size of the separator exceeds the above range, short circuits are likely to occur. When the amount of the conductive material is within the above range, the resistance of the film can be suppressed while preventing a short circuit, and the electrochemical device can have good rate characteristics.

[0127] V. Electrochemical device assembly The electrochemical device assembly includes an electrode assembly, a current collecting structure, an outer case, and a protective element. nothing.

[0128] Electrode Assembly The electrode assembly has a laminated structure in which the positive electrode and the negative electrode are laminated with the separator interposed therebetween. The positive electrode and the negative electrode are wound in a spiral shape with the separator interposed therebetween. In some embodiments, the battery volume includes an electrode assembly. The mass ratio of the electrode assembly (electrode assembly occupancy rate) is more than 40% or 50% In some embodiments, the electrode assembly occupancy is less than 90% or greater than 80%. In some embodiments, the electrode assembly occupancy is less than any of the above. When the electrode assembly occupancy rate is within the above range, While maintaining the capacity of the electrochemical device, the repeated charge / discharge characteristics and high temperature retention due to the increase in internal pressure are improved. It is possible to suppress the deterioration of characteristics such as the presence of oxygen, and further to prevent the operation of the gas release valve. can.

[0129] Current collection structure The current collecting structure is not particularly limited. In some embodiments, the current collecting structure includes a wiring portion and This structure reduces the resistance of the joint. When the electrode assembly has the above-mentioned laminated structure, In this case, a structure in which the metal core portions of the electrode layers are bundled and welded to a terminal is preferably used. As the electrode area increases, the internal resistance also increases. Therefore, two or more terminals are provided in the electrode. It is also preferable to use the electrode assembly having the above-mentioned wound structure to reduce the resistance. In this case, two or more lead structures are provided on the positive and negative electrodes, and they are bundled together at the terminals. The internal resistance can be reduced.

[0130] Outer case The material of the exterior case is not particularly limited as long as it is a substance that is stable against the electrolyte solution used. The exterior case is made of nickel-plated steel, stainless steel, aluminum or aluminum alloy. , metals such as magnesium alloys, or laminated films of resin and aluminum foil are used, In some embodiments, the outer casing is made of aluminum or It is made of aluminum alloy metal or laminated film.

[0131] Metal exterior cases are welded together by laser welding, resistance welding, or ultrasonic welding. or a rivet using the above-mentioned metals via a resin gasket. The outer case using the above-mentioned laminated film includes, but is not limited to, a laminated structure. The sealing structure includes, but is not limited to, a sealing structure formed by heat-sealing resin layers together. In order to improve the properties, a resin different from the resin used in the laminated film is used between the above-mentioned resin layers. In the case where the resin layer is heat-sealed via the current collecting terminal to form a sealed structure, Since the resin is bonded to the polymer, the intermediate resin is a resin having a polar group or a polymer having a polar group introduced therein. Modified resin is used. The shape of the outer case is also arbitrary, for example, cylindrical, rectangular, etc. The display may be of any one of the following types: laminate type, button type, large type, etc.

[0132] Protection Device As a protective element, it is a positive temperature coefficient that increases resistance when abnormal heat is generated or a very large current flows. Number (PTC), temperature fuse, thermistor, internal pressure or temperature of the battery when abnormal heat is generated Valves that cut off the current flowing through an electric circuit by suddenly increasing the temperature (current cutoff valves) The above-mentioned protection elements can be selected so that they do not operate during normal use at high currents. Even if a device is designed to not generate abnormal heat or thermal runaway without a protective element, good.

[0133] VI. Application The electrochemical device of the present invention includes any device in which an electrochemical reaction occurs. Specific examples thereof include , including all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In addition, the electrochemical device can be used in lithium metal secondary batteries, lithium ion secondary batteries, and lithium heavy batteries. Lithium secondary batteries, including combined secondary batteries or lithium ion polymer secondary batteries.

[0134] The present invention further provides an electronic device comprising an electrochemical device according to the present invention.

[0135] The application of the electrochemical device of the present invention is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the electrochemical device of the present invention may include a notebook PC. Computers, pen-input computers, mobile computers, e-book players, mobile phones, Fax, mobile copy, mobile printer, headphone stereo, video movie, liquid LCD TVs, handheld cleaners, portable CDs, mini discs, transceivers, Child notebook, calculator, memory card, portable tape recorder, radio, backup power supply, motors, automobiles, motorcycles, mopeds, bicycles, lighting equipment, toys, games, watches , power tools, strobes, cameras, large household batteries and lithium ion capacitors, etc. These can be used, but are not limited to these.

[0136] The following takes a lithium ion battery as an example, and describes the lithium ion battery with reference to specific examples. The preparation of a lithium-ion battery is described below, and those skilled in the art will recognize that the preparation methods described in this invention are merely exemplary. It is understood that these are merely exemplary and that any other suitable preparation methods are within the scope of the present invention. It should be.

[0137] Working Example The following describes the lithium ion battery of the present invention through examples and comparative examples. The on-battery is explained and its performance is evaluated.

[0138] 1. Preparation of lithium-ion batteries 1. Preparation of the negative electrode Artificial graphite, styrene-butadiene rubber, and sodium carboxymethyl cellulose Mix with deionized water in a mass ratio of 96%:2%:2% and stir evenly to obtain a slurry for the negative electrode. This negative electrode slurry was applied to a 12 μm copper foil, dried, cold rolled, and punched. A tab was then welded to obtain a negative electrode.

[0139] 2. Preparation of the positive electrode The positive electrode active material, conductive material (Super-P), and polyvinylidene fluoride (PVDF) are mixed together. Mix with N-methylpyrrolidone (NMP) in a ratio of 95%:2%:3% and add auxiliary agents. The slurry for the positive electrode was mixed with 12 μm aluminum particles. The positive electrode was obtained by applying the mixture to a aluminum foil, drying, cold rolling, punching, and welding a tab.

[0140] The positive electrode active materials used in the examples and comparative examples were commercially available products, and the specific examples are shown in the following table. That is correct.

[0141] JPEG0007660237000001.jpg81152

[0142] The auxiliary agents used in the examples or comparative examples are shown in the table below.

[0143] JPEG0007660237000002.jpg62152

[0144] 3. Preparation of electrolyte In a dry argon gas atmosphere, EC, PC, PP, and DEC (weight ratio 1:1:1:1 ) was mixed, LiPF6 and lithium difluorophosphate were added, and the mixture was mixed uniformly. The electrolyte solution was formed. Here, the concentration of LiPF6 was 1.15 mol / L. By adding additives with different contents, different electrolyte solutions of the examples and comparative examples were obtained.

[0145] The components of the electrolyte solutions used in the examples are shown in the table below.

[0146] JPEG0007660237000003.jpg47152

[0147] 4. Preparation of the separator A polyethylene (PE) porous polymer film was used as the separator.

[0148] 5. Preparation of Lithium-ion Battery The obtained positive electrode, separator, and negative electrode were wound in this order and placed in an exterior foil, leaving a liquid injection hole. The electrolyte is injected through the opening, then sealed, and the process of formation and capacity measurement are carried out. A lithium-ion battery was obtained.

[0149] 2.Measurement method 1. Method for measuring the thickness change rate of the positive electrode mixture layer The positive electrode was punched out into a disk shape with a diameter of 14±0.2 mm to prepare a test piece. The thickness (t0) of the test piece was measured. The test piece was immersed horizontally in diethyl carbonate and heated to 85 The test pieces were left to stand at a temperature of ±1°C for 120±0.3 hours. After the immersion was complete, they were taken out and soaked in water at room temperature. After leaving the test piece flat for 30 minutes, the thickness (t1) of the center of the test piece was measured using the following formula: The thickness change rate of the positive electrode mixture layer was calculated. Thickness change rate = (t1-t0) / t0 x 100%.

[0150] 2. Method for measuring the reaction area (Y) of the positive electrode mixture layer Using a surface area meter (fully automatic surface area measuring device manufactured by Ohkura Riken), samples were taken at 350°C under nitrogen flow. After pre-drying the pipe for 15 minutes, the relative pressure of nitrogen gas to atmospheric pressure was precisely 0.3. Using the adjusted nitrogen / helium mixed gas, the nitrogen adsorption BET one-point method using gas flow was used. Specific surface area of ​​the positive electrode mixture layer (m 2 The reaction area ( Y) was calculated. Y = specific surface area of ​​positive electrode mixture layer × weight of positive electrode mixture layer.

[0151] 3. Measurement method for intermittent cycle capacity retention rate of lithium-ion batteries At 50°C, a lithium-ion battery is charged at a constant current of 0.5C up to 4.45V. Charge at a constant current of 0.05C, leave it for 20 hours, then charge at 0.5C up to 3.0V. The lithium ion battery was discharged at a constant current and the above operation was regarded as the first cycle. The battery was cycled 200 times. "1C" means that the capacity of the lithium-ion battery is depleted within one hour. The current value for fully discharging a lithium-ion battery is given by the following formula: The retention rate of the capacity of the cylinder was calculated. Intermittent cycle capacity retention rate = (discharge capacity after 200 cycles / discharge capacity of the first cycle) ×100%.

[0152] 4. Measurement method for float charging characteristics of lithium-ion batteries At 25°C, the lithium-ion battery was charged at a constant current of 0.5C to 4.45V, and The lithium-ion battery was then charged at a constant voltage of 4.45 V to 0.05 C. Place the battery in a 4.45V oven and charge it at a constant voltage of 4.45V (until the current reaches 20mA). The thickness change of a lithium-ion battery was monitored. The increase in thickness of a lithium-ion battery exceeds 20% based on the thickness of a lithium-ion battery. Lithium-ion batteries are float-charged at 50°C until they expire. The time taken was recorded.

[0153] 3. Measurement results Table 1 shows the characteristics of the lithium ion battery, and the thickness change rate of the positive electrode mixture layer in each example and comparative example. In the examples and comparative examples shown in Table 1, the positive electrode active material is Material 1. The lithium difluorophosphate content is 0.2 wt %.

[0154] [Table 1]

[0155] As can be seen from the results, the auxiliary agent and its content affect the thickness change rate of the positive electrode mixture layer. The positive electrode mixture layer was immersed in diethyl carbonate at 85° C. for 120 hours, and then If the thickness change rate of the positive electrode mixture layer is less than 10%, the intermittent cycle Capacity retention rate (at least 20%) and float charge time until expiration (5 to 10 times The intermittent cycle characteristics of lithium ion batteries can be significantly improved. The positive electrode mixture layer is heated to 85°C with diethyl ether, and the charge stability and float charge characteristics are significantly improved. After immersion in polycarbonate for 120 hours, the thickness change rate of the positive electrode mixture layer is less than 10%. In addition, by controlling the content of the auxiliary agent to 3000 ppm or less, the lithium-ion The intermittent cycle characteristics and float charge characteristics of the ON battery can be further improved. .

[0156] Table 2 shows the effect of the content of lithium difluorophosphate in the electrolyte on the characteristics of lithium-ion batteries. Comparative Examples 6 to 7 and Examples 8 to 12 show the effect of the compositions containing the compounds listed in Table 2. Only the amount differs from Example 3.

[0157] [Table 2]

[0158] As can be seen from the results, when the content of lithium difluorophosphate in the electrolyte was 0.001 Within the range of 100% to 200% by weight, lithium-ion batteries showed significantly improved intermittent It has cycle characteristics and float charge characteristics.

[0159] Table 3 shows the effect of the positive electrode active material on the characteristics of the lithium ion battery. Example 1 differs from Example 3 only in the positive electrode active materials listed in Table 3.

[0160] [Table 3]

[0161] As can be seen from the results, the positive electrode active material is made of two types of lithium-containing transition metal oxides with different median diameters. The inclusion of these compounds further improves the intermittent cycling and float charging characteristics of lithium-ion batteries. The lithium-containing transition metal oxide can be improved to the above. When the alloy contains at least one metal element selected from the group consisting of Nb, Al, and Sn, the alloy can be made of lithium. The improvements in intermittent cycling and float charging characteristics of the lithium-ion battery are particularly notable.

[0162] Table 4 shows the relationship between the weight of lithium difluorophosphate and the reaction area of ​​the positive electrode mixture layer. Examples 18 to 21 show the effect of the parameters listed in Table 4 on the properties of the on-cell battery. Only the meter is different from the third embodiment.

[0163] [Table 4]

[0164] As can be seen from the results, the content of lithium difluorophosphate in the electrolyte is X mg and Reaction area of ​​the positive electrode mixture layer Y m 2 If X / Y satisfies 10≦X / Y≦100, the lithium-ion battery This contributes to further improvement of the intermittent cycle characteristics and float charge characteristics of the battery.

[0165] Table 5 shows the effect of additives in the electrolyte on the characteristics of the lithium-ion battery. 22 to 29 differ from Example 3 only in the parameters listed in Table 5.

[0166] [Table 5]

[0167] As can be seen from the results, the electrolyte contains dinitrile compounds, trinitrile compounds, sultones and and / or fluorocarbonates, which may improve the intermittent cycling of lithium-ion batteries. This contributes to further improvement of the characteristics and float charging characteristics.

[0168] Table 6 shows the effect of the solvent in the electrolyte on the characteristics of the lithium ion battery. 0 to 32 differ from Example 3 only in the solvent of the electrolyte solution listed in Table 6. 10 differs from Comparative Example 1 only in the solvent of the electrolyte, which is listed in Table 6.

[0169] [Table 6]

[0170] As can be seen from the results, the electrolyte solvent is a combination of cyclic carbonate and chain carbonate. Combinations of carbonates and carboxylic acid esters, including lithium It is possible to further significantly improve the intermittent cycle characteristics and float charge characteristics of ion batteries. can.

[0171] Throughout the specification, the terms "an embodiment," "part of an embodiment," "one embodiment," "another example," etc. Any reference to "an example," "an embodiment," or "part of an example" is to at least one embodiment of the invention. Examples or embodiments include the specific features, structures, materials, or characteristics described in the example or embodiment. Therefore, the following statements are made throughout the specification, e.g., "Some "In an embodiment," "in an embodiment," "in one embodiment," "in another embodiment" The terms "in one example," "in a particular example," or "example" do not necessarily represent the invention. The present disclosure is not intended to cite the same embodiment or examples as those described herein. The materials or features may be combined in any suitable manner in one or more embodiments or examples. It can be combined.

[0172] Although exemplary embodiments have been described and illustrated, those skilled in the art will recognize that the above-described embodiments are not intended to limit the present invention. and does not depart from the spirit, principle, and scope of the present invention. It should be understood that modifications, substitutions and alterations to the examples are possible in some cases.

Claims

1. An electrochemical device including a positive electrode, a negative electrode, and an electrolyte, the positive electrode includes a positive electrode current collector and a positive electrode mixture layer formed on the positive electrode current collector, The electrolyte solution contains lithium difluorophosphate, and the content of the lithium difluorophosphate is 0.001 wt % to 2 wt % based on the total weight of the electrolyte solution; After the positive electrode mixture layer is immersed in diethyl carbonate at 85° C. for 120 hours, the thickness change rate of the positive electrode mixture layer is less than 10%; the content X mg of the lithium difluorophosphate in the electrolyte and the reaction area Y m 2 of the positive electrode mixture layer satisfy 10≦X / Y≦100.

2. The electrochemical device according to claim 1 , wherein the electrolyte solution contains a carbonate, the carbonate containing a cyclic carbonate and a chain carbonate.

3. 10. The electrochemical device of claim 1, wherein the electrolyte comprises a carbonate and a carboxylic acid ester.

4. The electrochemical device according to claim 1 , wherein the positive electrode mixture layer contains an auxiliary having a hydrophilic group and a lipophilic group.

5. The coagent has at least one of the following characteristics: (a) an oxidation potential of 4.5 V or more and a reduction potential of 0.5 V or less; (b) the surface tension is 40 mN / m or less; (c) contains an unsaturated carboxylic acid group; (d) The electrochemical device according to claim 4, wherein the content of the auxiliary agent is 3000 ppm or less based on the total weight of the positive electrode mixture layer.

6. 5. The electrochemical device of claim 4, wherein the co-agent comprises at least one of 2-dodecyl acrylate, polyethylene glycol monomethyl ether acrylate, polyethylene glycol dimethacrylate, (2-ethylhexyl)acrylate, acrylate non-ionic fluorocarbon surfactants, dodecyl methacrylate, acrylic acid ester copolymers, maleic acid-acrylic acid copolymers, or ethylene-acrylic acid copolymers.

7. 10. The electrochemical device of claim 1, wherein the electrolyte further comprises at least one of a dinitrile compound, a trinitrile compound, a sultone, a fluorocarbonate, or an unsaturated ethylene carbonate.

8. The electrochemical device according to claim 1 , wherein the positive electrode mixture layer contains a positive electrode active material, and the positive electrode active material contains lithium-containing transition metal oxides having different median diameters.

9. The lithium-containing transition metal oxide contains a compound represented by general formula (1), <h2 style=";text-align:left;direction:ltr">Li<h2 style=";text-align:left;direction:ltr"> a <h2 style=";text-align:left;direction:ltr"> 11<h2 style=";text-align:left;direction:ltr"> b <h2 style=";text-align:left;direction:ltr"> 12<h2 style=";text-align:left;direction:ltr"> c <h2 style=";text-align:left;direction:ltr"> 13<h2 style=";text-align:left;direction:ltr"> d <h2 style=";text-align:left;direction:ltr"> O<h2 style=";text-align:left;direction:ltr"> 2 <h2 style=";text-align:left;direction:ltr"> (1) M1 is at least one selected from Co, Ni, or Mn; M2 is at least one selected from Mg, Ti, Zr, Ge, Nb, Al, or Sn; M3 is an element other than Li, M1 and M2; a, b, c and d are 0.5≦a<1.1, 0.8≦b<1.2, 0.002≦c≦0.05, and The electrochemical device according to claim 8 , wherein 0≦d≦0.05 is satisfied.

10. 9. The electrochemical device according to claim 8, wherein the lithium-containing transition metal oxide contains Mg and at least one metal element selected from the group consisting of Ti, Zr, Ge, Nb, Al, and Sn.

11. An electronic device comprising an electrochemical device according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Non-aqueous electrolyte and lithium ion battery

    CN110911753A

  • Lithium secondary battery

    JP2013143381A

  • Nonaqueous secondary battery

    JP2019029215A

  • Rechargeable lithium battery

    US20150288033A1

  • Electrolyte solution, electrochemical device, secondary battery, and module

    WO2018016245A1